SISTEM PAKAR PENGIDENTIFIKASI HAMA PADA TANAMAN ANGGREK TERESTRIAL BERBASIS MOBILE - Satia Suhada; Taufik Hidayatulloh (Universitas Bina Sarana Informatika Kota Sukabumi, 2014)
Expert System Identifiers Terrestrial Orchids Pests Based Mobile. Orchid is a high aesthetic value of ornamental plants and are important in the flower trade. In 2002, Indonesia exported orchid cut flowers as much as 1,975,595 kg valued at U.S. 2,752,281 and in 2003 decreased to 1,275,305 kg valued at U.S. 3,741,560. One cause of the decline in exports of cut orchid flowers is causedby a number of pests that attack the orchid plants. Pest is one of the important issues to be considered in the production of business plants in general, because the pest is able to reduce significantly the production of both qualitative and quantitative. Therefore it is necessary for early treatment to control these pests on orchids. Based on the description, needed a system that could represent an expert who has the knowledge base and experience in the terrestrial orchid, which is an expert system.Later in 2013, the trend in mobile based technologies more rapidly. Therefore, in order to obtain the value of information more quickly and flexibly, this expert system will be applied in the form of Android-based mobile applications.